K. H. Djazuli's Action in Teaching the Qodiriyah Wa Naqsabandiyah Order to the Srumbung Magelang Village Community - Sari, Hidayatul Luthfiyyati; Syarifah, Hidayatu (El Tarikh : Journal of History, Culture and Islamic Civilization, 2022)
The focus of research is Kiprah K. H. Djazuli in teaching Tarekat Qodiriyah wa Naqsabandiyah in Srumbung District, Magelang in 1990-2008. This study uses the sociological approach of functional religion proposed by Emile Durkheim. The sociological approach of functional religion was used by researchers to determine the function of the teachings of the Tarekat Qodiriyah wa Naqsabandiyah which were brought and introduced by K. H. Djazuli for the social life of the people of Srumbung District. This study uses the social role theory to reveal the progress and role of K. H. Djazuli for the development of the Qodiriyah wa Naqsabandiyah teachings in Srumbung District. The result of this research is that K. H. Djazuli plays an important role in the development of the Qodiriyah wa Naqsabandiyah Tarekat in Srumbung District, the role played by K. H. Djazuli in developing the teachings of the Qodiriyah wa Naqsabandiyah Tarekat, among others, is the role in the field of religion is to conduct da'wah by means of staying in touch with each resident's house. Its role in the social field is to change the behavior and attitudes of the community for the better than before. His role in the education sector is to participate in establishing teaching facilities for people who are still lacking in recognizing the letters of the alphabet, and also initiating the establishment of formal schools in the Roudlatul Falaah Islamic Boarding School, Srumbung, namely RA, MI, SMP, SMA.